Research progress and design optimization of CAR‐T therapy for pancreatic ductal adenocarcinoma. (3rd July 2019) - Li, Tianjiao; Li, Hao; Li, Shuo; Xu, Shuaishuai; Zhang, Wuhu; Gao, Heli; Xu, Huaxiang; Wu, Chuntao; Wang, Wenquan; Yu, Xianjun; Liu, Liang
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a highly malignant cancer with limited treatment options. Chimeric antigen receptor T cells (CAR‐T) are genetically engineered T cells that can specifically kill tumor cells without major histocompatibility complex restriction. Encouraging progress in CAR‐T therapy for PDAC has been made in preclinical and early phase clinical trials. Challenges in CAR‐T therapy for solid tumors still exist, including immunosuppressive microenvironment, interstitial barrier, poor chemotaxis, and the "on‐target, off‐tumor" effect. Applying neoantigens of PDAC as targets for CAR‐T therapy, recognizing the CAR‐T subgroup with better antitumor effect, and designing a CAR‐T system targeting stroma of PDAC may contribute to develop a powerful CAR‐T therapy for PDAC in the future. Abstract : Encouraging progress in CAR‐T therapy for PDAC has been made in preclinical and early phase clinical trials. Challenges in CAR‐T therapy for solid tumors still exist, including immunosuppressive microenvironment, interstitial barrier, poor chemotaxis, and the "on‐target, off‐tumor" effect. Applying neoantigens of PDAC as targets of CAR‐T, recognizing the subgroups of CAR‐T cells with better antitumor effects, and designing a CAR‐T system targeting stroma of PDAC may contribute to develop a powerful CAR‐T therapy for PDAC.